(untitled) (Global Journal of Management and Business Research, 2015)
We analyze the single cycle and multiple cycles of confirming storage and factoring financing portfolio and introduce their business process. Then from the perspective of banks and medium and small companies, we construct the model of cost-benefit analysis to figure out the influential factors of the cost and benefit of both parties. Next we compare the ROE of both parties in the single supply chain financial product with that in the portfolio based on the single cycle of the portfolio. Finally we apply the dynamic game theory to produce the equilibrium point to assist decision making. This study shows that the net profits of both the banks and moneyborrowing companies are better in the confirming storage and factoring financing portfolio comparing to single factoring financing, which indicates a Pareto improvement. The ROE of money-borrowing companies increase as the ratio of first deposit increases.